Low-carbon sulfoaluminate cement and method for producing the same

CN122831574BActive Publication Date: 2026-11-03YICHENG ANDA SPECIAL ENG MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611269496.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-11-03
Estimated Expiration
2046-08-20

AI Technical Summary

Technical Problem

Existing low-carbon sulfoaluminate cements struggle to effectively improve long-term performance stability while maintaining early-stage strength, and the large amount of industrial solid waste added leads to significant early-stage strength loss. Existing modification technologies have failed to effectively address this issue in a synergistic manner.

Method used

A step-by-step grinding process and a composite activator (calcium nitrate and citric acid) are used to treat steel slag powder. Through mechanical activation and chemical activation, the inert layer on the surface of the steel slag is broken, promoting the dissolution of internal active components. The growth of hydration products is optimized by complexing and regulating with citric acid, thereby achieving a synergistic improvement in early strength and long-term stability.

Benefits of technology

While maintaining high early strength, it significantly improves the long-term strength development performance of cement, enhances the utilization rate of industrial solid waste resources, reduces cement production costs and carbon emissions, and avoids the problem of later strength reduction in traditional sulfoaluminate cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a preparation method of low-carbon sulphoaluminate cement, which comprises the following steps: 1) weighing raw materials, wherein the raw materials and the weight percentage thereof comprise 30-98 parts of sulphoaluminate cement clinker, 1-42 parts of steel slag powder, 1-42 parts of blast furnace slag powder, 12-21 parts of gypsum, 1-8 parts of limestone powder and 1.8-4.6 parts of composite activator; 2) performing grinding treatment on the composite activator and the steel slag powder to obtain modified steel slag powder, wherein the grinding treatment step comprises the following steps: firstly, performing grinding on the steel slag powder; then, adding the composite activator to perform common grinding; and 3) uniformly mixing the sulphoaluminate cement clinker, the gypsum, the limestone powder, the modified steel slag powder and the blast furnace slag powder to obtain the low-carbon sulphoaluminate cement. While realizing high-mixing-amount resource utilization of solid wastes such as steel slag and slag, the application can effectively guarantee the durability of the cement, has excellent early strength and continuously developed late strength, and is suitable for a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials, specifically relating to a low-carbon sulfoaluminate cement and its preparation method. Background Technology

[0002] Low-carbon sulfoaluminate cement, as a special cementitious material that reduces environmental impact, inherits the advantages of traditional sulfoaluminate cement such as early strength, rapid hardening, and impermeability and corrosion resistance. It also strives to significantly reduce carbon emissions and resource consumption by utilizing industrial solid waste, making it a promising low-carbon building material. However, its performance optimization faces a core challenge: while maintaining and improving the long-term performance stability of cement, it is necessary to effectively guarantee its early strength.

[0003] To improve the long-term performance of low-carbon sulfoaluminate cement, existing technologies typically employ the method of incorporating large proportions of solid waste such as fly ash. However, this often fails to maintain its inherent early-strength advantage while improving later-stage stability, and may introduce new problems related to workability, shrinkage, or cost. On the other hand, the green transformation of the cement industry is becoming increasingly important, and large-scale resource utilization of industrial solid wastes such as steel slag and blast furnace slag has become an important development direction. However, traditional solid wastes generally have low cementitious activity, and direct incorporation in large quantities can lead to a significant decline in the early-stage performance of cement.

[0004] To address the aforementioned issues, activating solid waste with chemical activators is a common improvement approach. However, this often focuses on enhancing early strength, with insufficient synergistic effects on improving the long-term strength stability of sulfoaluminate cement, and lacks systematic regulation of the hydration process of the solid waste-sulfoaluminate cement composite system. Existing modification technologies have failed to effectively address the dual challenges of synergistic activation of activity and ensuring the long-term strength stability of sulfoaluminate cement under high solid waste content. Further development of green, low-carbon sulfoaluminate cement that can effectively and synergistically solve the problems of later-stage strength stability and high-value utilization of solid waste without sacrificing early performance has significant technological and environmental implications. Summary of the Invention

[0005] The main objective of this invention is to address the problems of easy decline in later strength of existing sulfoaluminate cement, significant loss of early strength due to large amounts of industrial solid waste, and insufficient activation of solid waste activity. This invention provides a low-carbon sulfoaluminate cement and its preparation method, which can effectively stabilize the long-term performance of cement while realizing the resource utilization of high amounts of solid waste such as steel slag and blast furnace slag, so that it has both excellent early strength and continuously developing later strength.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing low-carbon sulfoaluminate cement includes the following steps: 1) Weigh all raw materials, and the weight percentages of each raw material include: 30-98 parts of sulfoaluminate cement clinker, 1-42 parts of steel slag powder, 1-42 parts of blast furnace slag powder, 12-21 parts of gypsum, 1-8 parts of limestone powder, and 1.8-4.6 parts of composite activator; the composite activator contains calcium nitrate and citric acid; the 7-day activity index of the steel slag powder is not less than 50%, and the 28-day activity index is not less than 60%; the 7-day activity index of the blast furnace slag powder is not less than 70%, and the 28-day activity index is not less than 95%. 2) The composite activator and steel slag powder are ground to obtain modified steel slag powder; the grinding process adopts a step-by-step grinding process, the specific steps of which include: first grinding the steel slag powder at a speed of 350~400 r / min; then adding the composite activator and grinding together at a speed of 400~450 r / min; 3) Dry mix the weighed sulfoaluminate cement clinker, gypsum, limestone powder, modified steel slag powder and blast furnace slag powder evenly to obtain the low-carbon sulfoaluminate cement.

[0007] Furthermore, the grinding process employs a step-by-step grinding technique, specifically including: first, grinding the steel slag powder at a speed of 350-400 r / min for 5-15 min for preliminary refinement; then, adding the composite activator and grinding together at a speed of 400-450 r / min (higher than the speed in the first step) for 30-60 min. Using the step-by-step grinding process described in this invention can significantly increase the effective contact area and depth of action between the composite activator and the active surface of the steel slag, promoting pre-activation and deep modification of the steel slag particle surface.

[0008] Preferably, in the composite activator, the mass ratio of calcium nitrate to citric acid is (5~15):1. Under this ratio, it is beneficial to fully utilize the chemical activating effect of calcium nitrate, through the highly diffusive NO3... - This process accelerates the removal of the inert layer on the surface of steel slag particles and the continuous dissolution of internal active minerals. Simultaneously, the mechanical activation effect of stepwise grinding achieves deep pre-modification of the steel slag surface, providing stable early strength growth momentum for the cement system. Furthermore, it leverages the complexation and regulation advantages of citric acid, guiding the uniform nucleation and orderly growth of hydration products such as ettringite, while inhibiting the formation of coarse, oriented crystals. This optimizes the pore structure, improves matrix density, and smooths the hydration exothermic process, ensuring the continuous and stable development of cement strength and improved durability in the later stages. It effectively avoids problems such as violent early hydration reactions and excessively strong crystal orientation of hydration products, which can lead to later microstructural deterioration, strength reduction, and decreased impermeability and durability. At the same time, it promotes and ensures good rapid-hardening and early-strength performance.

[0009] Furthermore, the content of calcium nitrate in the steel slag cementitious activator is 1.6~3.8 parts, and the content of citric acid is 0.16~0.38 parts.

[0010] Preferably, the composite activator further comprises triisopropanolamine (TIPA), with a mass ratio of 0.05 to 0.12:1 to calcium nitrate.

[0011] The synergistic mechanism of the composite activator in the cementitious system of this invention includes the following: First, the composite activator is pre-milled with steel slag. Under the mechanical impact and shear force provided by the stepwise gradient-controlled milling process, the particle size of the steel slag is reduced, the specific surface area is increased, and the hydration inert layer (such as a dense iron-magnesium phase shell) on its surface is continuously broken, exposing the internal silicate and aluminoferrite minerals. Furthermore, the introduced composite activator can immediately adsorb and act on these fresh high-energy surfaces, pre-regulating and modifying their surface chemical state. When the resulting modified steel slag powder encounters the sulfoaluminate cement clinker system in the subsequent mixing stage, it can act more quickly and concentratedly on the deep activation and long-term hydration process regulation.

[0012] In subsequent reactions, the calcium nitrate introduced dissociates to produce Ca. 2+ With NO3 - In the ion pair, NO3 - As a highly diffusive anion, it can accelerate the migration and exchange of ions within the slurry, which helps to further disrupt the passivation layer on the surface of steel slag particles and promotes the early dissociation of their internal active components (such as C2S). Furthermore, the introduced citric acid and triisopropanolamine molecules act as highly efficient surface activity regulators, with their carboxyl and amine groups preferentially adsorbing onto specific crystal faces of growing hydration product crystals (such as Ca(OH)2 and AFt). This selective adsorption helps to alter the relative growth rates of different crystal faces, inhibiting the formation of coarse, highly oriented Ca(OH)2 crystals, thereby optimizing the pore structure and improving compressive strength. Simultaneously, citric acid integrates free metal ions in the slurry, reducing local ion supersaturation and making the nucleation and growth process of hydration products (especially AFt) more uniform, which is beneficial for steel slag dissolution. By regulating the ion migration rate and the solid-liquid interface reaction process through the above methods, the reaction pathway from particle dissolution to product precipitation can be synergistically optimized, effectively stimulating solid waste activity and constructing a hardened microstructure with superior mechanical properties and better long-term stability.

[0013] Preferably, when the steel slag powder content is 12-42 parts, the mass ratio of steel slag powder to composite activator is 1:0.1-1:0.5. Under this ratio, problems such as incomplete activation of steel slag, delayed early strength development, and weak later strength growth due to insufficient activator dosage can be effectively avoided, fully tapping the cementitious potential of steel slag solid waste. At the same time, it can effectively ensure the cost of raw materials and avoid the drawbacks of excessively rapid early hydration rate and abnormally shortened setting time, ultimately achieving a coordinated unity of steel slag activation effect, cement comprehensive performance, and economy.

[0014] Furthermore, the sulfoaluminate cement clinker contains 36-64 wt.% CaO and 20-36 wt.% Al2O3.

[0015] Furthermore, the gypsum is natural gypsum, wherein the CaO content is 35~63 wt.% and the SO3 content is 41~73 wt.%.

[0016] Furthermore, the limestone powder contains 32-56 wt.% CaO and 14-25 wt.% SiO2.

[0017] Furthermore, the CaO content in the steel slag powder is 23~41 wt.%, and the Fe2O3 content is 28~49 wt.%.

[0018] Furthermore, the CaO content in the blast furnace slag powder is 35~62 wt.%, and the SiO2 content is 23~41 wt.%.

[0019] Furthermore, the specific surface area of ​​the sulfoaluminate cement clinker is 400~450 m². 2 / kg, density is 3~3.8 g / cm³ 3 The specific surface area of ​​natural gypsum is 350~400 m². 2 / kg; the density of limestone powder is 2.5~3.2 g / cm³. 3 The specific surface area of ​​steel slag powder is 320~400 m². 2 / kg, density is 3.2~4.0 g / cm³ 3 The activity index at 7 days is not less than 50%, and the activity index at 28 days is not less than 60%; the density of blast furnace slag powder is 2.5~3.0 g / cm³. 3 Specific surface area is 380~440m² 2 / kg, with an activity index of not less than 70% at 7 days and not less than 95% at 28 days.

[0020] Furthermore, all raw materials must be in a dry state before pretreatment.

[0021] Furthermore, the sulfoaluminate cement clinker, blast furnace slag powder, and natural gypsum are ground and sieved using a ball mill before use to obtain raw material powders that meet the requirements of specific surface area, density, etc.

[0022] Furthermore, the grinding process is carried out in a planetary ball mill with the following process parameters: ball-to-material mass ratio (5~10):1, grinding ball material is zirconium oxide, rotation speed is 400~450 r / min, and grinding time is 30~60 min.

[0023] Furthermore, the sieving refers to screening using a standard square-hole sieve with a mesh size of 0.9 mm, requiring that the residue of each raw material powder after sieving is less than 5%.

[0024] Furthermore, the cementitious activity of steel slag and blast furnace slag is significantly lower than that of sulfoaluminate cement clinker, and the composition of steel slag fluctuates greatly. The high iron content and the presence of free calcium oxide (f-CaO), if not properly treated, can affect the stability of the hydration process. To achieve high-volume resource utilization of steel slag and blast furnace slag in sulfoaluminate cement systems, the present invention specifically employs the following improvement methods: (1) In this invention, steel slag powder and composite activator are first subjected to gradient pre-grinding. While ensuring that the 28-day activity index of the steel slag powder is not less than 50%, the high Fe2O3 content (28~49wt.%) in the steel slag is utilized, and combined with calcium nitrate to provide NO3. - With Ca 2+ To create an environment with sufficient calcium and suitable alkalinity to promote Fe 3+ Participating in complexation reactions, the carboxyl groups and other components introduced in the composite activator can react with Fe. 3+ Al 3+ Polyvalent metal ions form complexes, and the amino group in triisopropanolamine can also react with Ca. 2+ The formation of complexes and the complexation-dissociation process continuously disrupt the inert layer on the surface of steel slag particles, promoting the continuous release of internal active components and effectively facilitating the dissolution of steel slag and the formation of AFt. Furthermore, because steel slag is rich in ferric phase, it can further react with aluminum phase and sulfate ions in the cement system during the later stages of hydration to generate more stable ferric hydration products (such as iron-containing ettringite and hydrated calcium aluminoferrite). This helps to refine the pore size and create a denser structure, providing support for promoting later-stage strength growth.

[0025] (2) The introduced composite activator can be activated by NO3 - Accelerating the migration and exchange of ions within the slurry, while utilizing citric acid to integrate free metal ions in the slurry and reducing local ion supersaturation, can effectively promote the dissolution of steel slag. This provides a guarantee for achieving early strength without loss and stable strength growth in the later stages under high solid waste content.

[0026] (3) In this invention, a composite activator is added to the steel slag during the grinding stage for pre-grinding, which can effectively improve grinding efficiency, promote the acquisition of finer particle size and higher specific surface area, and optimize particle size distribution. In addition, under the environment of a large amount of fresh surface and high mechanical activation energy generated by grinding, the introduced composite activator can more effectively play the role of pre-activation and surface modification, and more fully stimulate the potential cementitious activity of steel slag-based solid waste, which helps to achieve the synergistic improvement of early strength development and long-term durability of cement on a macroscopic level.

[0027] (4) This invention combines industrial solid waste raw materials with composite activators to achieve a multi-level synergistic promoting effect: the dicalcium silicate (C2S) and iron-containing components in steel slag can provide a potential source for long-term strength development and early hydration activity for the system; the active aluminosilicate glass rich in blast furnace slag can be effectively activated in an alkaline environment; the introduction of calcium nitrate can further provide an early alkaline environment and Ca 2+ Ions promote the dissolution of active components and the stable crystallization of hydration products; citric acid and triisopropanolamine can regulate the influence of impurity ions through integration and synergistically regulate the setting process. The above components work together to optimize the formation and stability of the microstructure of cement paste, effectively ensuring the continuous development of later strength while improving early strength, thereby synergistically compensating for the defects such as strength reduction of traditional sulfoaluminate cement.

[0028] Furthermore, the mixing in step 2) must be carried out in a dedicated mixer for a mixing time of no less than 5 minutes.

[0029] Further, the obtained cement slurry is poured into a mold, vibrated to form the specimen, and then cured together with the mold. After reaching the predetermined age, the specimen is demolded and transferred to a standard curing environment for continued curing to obtain the low-carbon sulfoaluminate cement specimen block.

[0030] Furthermore, the curing method is to cure in the mold (curing statically for 6 hours at a temperature of 20±2℃ and a humidity of not less than 90%), demold, and then perform standard curing (at a temperature of 20±2℃ and a humidity of not less than 95%) until the corresponding age.

[0031] This invention also provides a low-carbon sulfoaluminate cement prepared according to the above scheme, the properties of which include the following: initial setting time at standard consistency is 25-30 min, final setting time is 35-40 min, 1-day compressive strength is 25-35 MPa, 3-day compressive strength is 35-45 MPa, 28-day compressive strength is 43-50 MPa, 90-day compressive strength is 45-55 MPa, and 28-day chloride ion diffusion coefficient is ≤1.0×10⁻⁶. -12 m 2 / s.

[0032] Compared with the prior art, the present invention has at least the following beneficial effects: 1) This invention can effectively improve the resource utilization rate of industrial solid waste (steel slag powder, slag powder, etc.) in sulfoaluminate cement, and significantly reduce the raw material cost and carbon emissions of cement production.

[0033] 2) This invention optimizes the raw material system (functional component composite + proportion optimization) to make the high iron content in steel slag a favorable factor for constructing a stable microstructure; combined with the specific chemical environment created by the composite activator, Fe...3+ The iron phase is effectively integrated into the hydration reaction process, ultimately forming stable iron-containing hydrates such as iron-containing ettringite and amorphous iron-aluminate gel. In traditional processes, the iron phase in steel slag is mostly encased in a dense iron-magnesium phase shell, which not only makes it difficult for the internal active minerals to dissolve and participate in the hydration reaction, but also hinders the release of internal active components; even if a small amount of Fe is present... 3+ Dissolution also occurs rapidly as coarse, loose ferric hydroxide crystals, which not only fail to contribute to structural strength but also introduce harmful porosity defects, deteriorating the compactness and long-term stability of the cement matrix. This invention, however, breaks down the inert iron phase layer on the surface of the steel slag through the mechanical force of stepwise grinding, while simultaneously utilizing the complexing and regulating effect of citric acid in the composite activator to prevent Fe... 3+ Rapid agglomeration and precipitation enable it to participate in the hydration and crystallization process of the sulfoaluminate system at a controllable rate, achieving a functional transformation of high-iron phase solid waste that is traditionally difficult to utilize, and turning the originally unfavorable components into beneficial components that improve the long-term stability of the structure.

[0034] 3) Through the synergistic design of the raw material system and composite activator, the cement provided by this invention can effectively improve its long-term strength development performance while maintaining the high early strength of sulfoaluminate cement, avoiding the problems of slow or even shrinking strength in the later stage that are common in traditional sulfoaluminate cement, and achieving an effective combination of high performance and green and low-carbon properties. Detailed Implementation

[0035] The technical solutions adopted in this invention are described in detail below through specific implementation examples. These descriptions are merely a part of the invention and do not represent all embodiments. Unless otherwise specified, the experimental methods used in this invention are conventional methods, and the instruments and equipment used are commercial products in this technical field.

[0036] This invention is not limited to the embodiments described above. Those skilled in the art can make various improvements and modifications without departing from the principles of this invention, and these improvements and modifications are also considered within the scope of protection of this invention. Contents not described in detail in this specification are prior art known to those skilled in the art.

[0037] In the following examples, the sulfoaluminate cement clinker used contained 46 wt.% CaO and 26 wt.% Al2O3; the natural gypsum contained 45 wt.% CaO and 52 wt.% SO3; the limestone powder contained 40 wt.% CaO and 18 wt.% SiO2; the steel slag powder contained 29 wt.% CaO and 35 wt.% Fe2O3; and the blast furnace slag powder contained 44 wt.% CaO and 29 wt.% SiO2.

[0038] The sulfoaluminate cement clinker and natural gypsum used were supplied by Yicheng Anda Special Cement Co., Ltd., and the specific surface area of ​​the sulfoaluminate cement clinker was 445 m². 2 / kg, density is 3.38 g / cm³ 3 The specific surface area of ​​natural gypsum is 363 m². 2 / kg.

[0039] The steel slag powder used is converter steel slag powder with a specific surface area of ​​365 m². 2 / kg, density is 3.42 g / cm³ 3 The 7-day activity index was 59.3%, and the 28-day activity index was 69.8%, which met the requirements for secondary steel slag powder in GB / T 20491-2017 "Steel Slag Powder for Cement and Concrete".

[0040] The limestone powder used was produced by Huanggang Dingshun Concrete Co., Ltd., with a density of 2.84 g / cm³. 3 .

[0041] The slag powder used is S95 grade granulated blast furnace slag powder, supplied by Wuhan Wuxin New Building Materials Co., Ltd., with a density of 2.94 g / cm³. 3 Specific surface area is 415 m² 2 / kg, the activity index was 76% at 7 days and 98% at 28 days.

[0042] The calcium nitrate, citric acid, and triisopropanolamine used were all sourced from Sinopharm Group.

[0043] The mixing water used was tap water from Wuhan.

[0044] Example 1 The specific preparation steps of a low-carbon sulfoaluminate cement are as follows: 1) Weigh all raw materials, including: 54 parts of sulfoaluminate cement clinker, 12 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, and 2.42 parts of composite activator (2.2 parts of calcium nitrate and 0.22 parts of citric acid). 2) The weighed steel slag powder and the composite activator (calcium nitrate and citric acid) are pre-ground. The pre-grinding process adopts a step-by-step grinding process, which includes: first, placing the steel slag powder separately in a ball mill and grinding it at a speed of 350 r / min for 10 min to achieve preliminary refinement; then, adding the composite activator into the ball mill and continuing to grind it together with the refined steel slag powder at a speed of 400 r / min for 40 min to obtain modified steel slag powder. 3) The weighed sulfoaluminate cement clinker, natural gypsum, limestone powder and blast furnace slag powder are dry-mixed with the obtained modified steel slag powder to obtain a uniform dry mixture; thus, the low-carbon sulfoaluminate cement is obtained.

[0045] Further, the obtained low-carbon sulfoaluminate cement is mixed with water, wherein the mass ratio of total water to dry material is controlled at 0.45, and mechanical stirring is performed to obtain a uniform low-carbon sulfoaluminate cement paste.

[0046] Example 2 The specific preparation steps of a low-carbon sulfoaluminate cement are as follows: 1) Weigh all raw materials, and the weight percentages of each raw material include: 48 parts of sulfoaluminate cement clinker, 18 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, and 2.42 parts of composite activator (2.2 parts of calcium nitrate and 0.22 parts of citric acid). 2) The weighed steel slag powder and the composite activator (calcium nitrate and citric acid) are pre-ground. The pre-grinding process adopts a step-by-step grinding process, which includes: first, placing the steel slag powder separately in a ball mill and grinding it at a speed of 350 r / min for 10 min to achieve preliminary refinement; then, adding the composite activator into the ball mill and continuing to grind it together with the refined steel slag powder at a speed of 400 r / min for 40 min to obtain modified steel slag powder. 3) The weighed sulfoaluminate cement clinker, natural gypsum, limestone powder and blast furnace slag powder are dry-mixed with the obtained modified steel slag powder to obtain a uniform dry mixture; thus, the low-carbon sulfoaluminate cement is obtained.

[0047] Further, the obtained low-carbon sulfoaluminate cement is mixed with water, wherein the mass ratio of total water to dry material is controlled at 0.45, and mechanical stirring is performed to obtain a uniform low-carbon sulfoaluminate cement paste.

[0048] Example 3 The specific preparation steps of a low-carbon sulfoaluminate cement are as follows: 1) Weigh all raw materials, and the weight percentages of each raw material include: 42 parts of sulfoaluminate cement clinker, 24 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, and 2.42 parts of composite activator (2.2 parts of calcium nitrate and 0.22 parts of citric acid). 2) The weighed steel slag powder and the composite activator (calcium nitrate and citric acid) are pre-ground. The pre-grinding process adopts a step-by-step grinding process, which includes: first, placing the steel slag powder separately in a ball mill and grinding it at a speed of 350 r / min for 10 min to achieve preliminary refinement; then, adding the composite activator into the ball mill and continuing to grind it together with the refined steel slag powder at a speed of 400 r / min for 40 min to obtain modified steel slag powder. 3) The weighed sulfoaluminate cement clinker, natural gypsum, limestone powder and blast furnace slag powder are dry-mixed with the obtained modified steel slag powder to obtain a uniform dry mixture; thus, the low-carbon sulfoaluminate cement is obtained.

[0049] Further, the obtained green low-carbon sulfoaluminate cement is mixed with water, wherein the mass ratio of total water to dry material is controlled at 0.45, and mechanical stirring is performed to obtain a uniform low-carbon sulfoaluminate cement paste.

[0050] Example 4 The specific preparation steps of a low-carbon sulfoaluminate cement are as follows: 1) Weigh all raw materials, including: 36 parts of sulfoaluminate cement clinker, 30 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, and 2.42 parts of composite activator (2.2 parts of calcium nitrate and 0.22 parts of citric acid). 2) The weighed steel slag powder and the composite activator (calcium nitrate and citric acid) are pre-ground. The pre-grinding process adopts a step-by-step grinding process, which includes: first, placing the steel slag powder separately in a ball mill and grinding it at a speed of 350 r / min for 10 min to achieve preliminary refinement; then, adding the composite activator into the ball mill and continuing to grind it together with the refined steel slag powder at a speed of 400 r / min for 40 min to obtain modified steel slag powder. 3) The weighed sulfoaluminate cement clinker, natural gypsum, limestone powder and blast furnace slag powder are dry-mixed with the obtained modified steel slag powder to obtain a uniform dry mixture; thus, the low-carbon sulfoaluminate cement is obtained.

[0051] Further, the obtained low-carbon sulfoaluminate cement is mixed with water, wherein the mass ratio of total water to dry material is controlled at 0.45, and mechanical stirring is performed to obtain a uniform low-carbon sulfoaluminate cement paste.

[0052] Example 5 The specific preparation steps of a low-carbon sulfoaluminate cement are as follows: 1) Weigh all raw materials, including: 54 parts of sulfoaluminate cement clinker, 12 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, and 2.42 parts of composite activator (2 parts of calcium nitrate, 0.32 parts of citric acid, and 0.1 parts of TIPA). 2) The weighed steel slag powder and the composite activator (calcium nitrate and citric acid) are pre-ground. The pre-grinding process adopts a step-by-step grinding process, which includes: first, placing the steel slag powder separately in a ball mill and grinding it at a speed of 350 r / min for 10 min to achieve preliminary refinement; then, adding the composite activator into the ball mill and continuing to grind it together with the refined steel slag powder at a speed of 400 r / min for 40 min to obtain modified steel slag powder. 3) The weighed sulfoaluminate cement clinker, natural gypsum, limestone powder and blast furnace slag powder are dry-mixed with the obtained modified steel slag powder to obtain a uniform dry mixture; thus, the low-carbon sulfoaluminate cement is obtained.

[0053] Further, the obtained low-carbon sulfoaluminate cement is mixed with water, wherein the mass ratio of total water to dry material is controlled at 0.45, and mechanical stirring is performed to obtain a uniform low-carbon sulfoaluminate cement paste.

[0054] Example 6 The specific preparation steps of a low-carbon sulfoaluminate cement are as follows: 1) Weigh all raw materials, and the weight percentages of each raw material include: 54 parts of sulfoaluminate cement clinker, 12 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, and 2.42 parts of composite activator (2 parts of calcium nitrate, 0.2 parts of citric acid, and 0.22 parts of TIPA). 2) The weighed steel slag powder and composite activator (calcium nitrate, citric acid and TIPA) are pre-ground. The pre-grinding process adopts a step-by-step grinding process, specifically including: first, placing the steel slag powder alone in a ball mill and grinding it at a speed of 350 r / min for 10 min to achieve preliminary refinement; then, adding the composite activator into the ball mill and continuing to grind it together with the refined steel slag powder at a speed of 400 r / min for 40 min to obtain modified steel slag powder. 3) The weighed sulfoaluminate cement clinker, natural gypsum, limestone powder and blast furnace slag powder are dry-mixed with the obtained modified steel slag powder to obtain a uniform dry mixture; thus, the low-carbon sulfoaluminate cement is obtained.

[0055] Further, the obtained low-carbon sulfoaluminate cement is mixed with water, wherein the mass ratio of total water to dry material is controlled at 0.45, and mechanically stirred to obtain a uniform low-carbon sulfoaluminate cement slurry; then the obtained cement slurry is poured into a mold, vibrated to form, and then cured in the mold (static curing for 6 hours at a temperature of 20±2℃ and a humidity of not less than 90%). After demolding, the specimen is transferred to a standard curing environment for continued curing (curing at a temperature of 20±2℃ and a humidity of not less than 95% until the specified age) to obtain the low-carbon sulfoaluminate cement specimen block.

[0056] Example 7 The specific preparation steps of a low-carbon sulfoaluminate cement are as follows: 1) Weigh all raw materials, including: 32 parts of sulfoaluminate cement clinker, 12 parts of steel slag powder, 28 parts of blast furnace slag powder, 20 parts of natural gypsum, 8 parts of limestone powder, and 1.8 parts of composite activator (1.6 parts of calcium nitrate and 0.2 parts of citric acid). 2) The weighed steel slag powder and the composite activator (calcium nitrate and citric acid) are pre-ground. The pre-grinding process adopts a step-by-step grinding process, which includes: first, placing the steel slag powder separately in a ball mill and grinding it at a speed of 400 r / min for 10 min to achieve preliminary refinement; then, adding the composite activator into the ball mill and continuing to grind it together with the refined steel slag powder at a speed of 450 r / min for 40 min to obtain modified steel slag powder. 3) The weighed sulfoaluminate cement clinker, natural gypsum, limestone powder and blast furnace slag powder are dry-mixed with the obtained modified steel slag powder to obtain a uniform dry mixture; thus, the low-carbon sulfoaluminate cement is obtained.

[0057] Further, the obtained low-carbon sulfoaluminate cement is mixed with water, wherein the mass ratio of total water to dry material is controlled at 0.4, and mechanical stirring is performed to obtain a uniform low-carbon sulfoaluminate cement paste.

[0058] Example 8 The specific preparation steps of a low-carbon sulfoaluminate cement are as follows: 1) Weigh all raw materials, including: 82 parts of sulfoaluminate cement clinker, 1 part of steel slag powder, 1 part of blast furnace slag powder, 12 parts of natural gypsum, 4 parts of limestone powder, and 4.4 parts of composite activator (4 parts of calcium nitrate and 0.4 parts of citric acid). 2) The weighed steel slag powder and the composite activator (calcium nitrate and citric acid) are pre-ground. The pre-grinding process adopts a step-by-step grinding process, which includes: first, placing the steel slag powder separately in a ball mill and grinding it at a speed of 350 r / min for 15 min to achieve preliminary refinement; then, adding the composite activator into the ball mill and continuing to grind it together with the refined steel slag powder at a speed of 400 r / min for 60 min to obtain modified steel slag powder. 3) The weighed sulfoaluminate cement clinker, natural gypsum, limestone powder and blast furnace slag powder are dry-mixed with the obtained modified steel slag powder to obtain a uniform dry mixture; thus, the low-carbon sulfoaluminate cement is obtained.

[0059] Further, the obtained low-carbon sulfoaluminate cement is mixed with water, wherein the mass ratio of total water to dry material is controlled at 0.5, and mechanical stirring is performed to obtain a uniform low-carbon sulfoaluminate cement paste.

[0060] Comparative Example 1 A low-carbon sulfoaluminate cement is prepared in a manner similar to that of Example 1, except that no composite activator is added during the steel slag grinding stage; and calcium nitrate and citric acid are mixed and stirred evenly with the dry mixture before the mechanical stirring described in step 3).

[0061] Comparative Example 2 A low-carbon sulfoaluminate cement is prepared in a manner largely similar to that of Example 1, except that the 28-day activity index of the steel slag powder used is 45%, and the 28-day activity index of the blast furnace slag powder is 90%. Other preparation and curing methods are the same as those in Example 1.

[0062] Comparative Example 3 A low-carbon sulfoaluminate cement is prepared in a manner similar to that of Example 1, except that the raw materials used and their weight percentages include: 54 parts of sulfoaluminate cement clinker, 12 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, and 2.42 parts of calcium nitrate (only 2.42 parts of calcium nitrate are added during the pre-grinding stage of steel slag).

[0063] Comparative Example 4 A low-carbon sulfoaluminate cement is prepared in a manner similar to that of Example 1, except that the raw materials used and their weight percentages include: 54 parts of sulfoaluminate cement clinker, 12 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, and 2.42 parts of citric acid (only 2.42 parts of citric acid are added during the pre-grinding stage of steel slag).

[0064] Comparative Example 5 A low-carbon sulfoaluminate cement is prepared in a manner largely similar to that of Example 1, except that the raw materials used and their weight percentages include: 54 parts of sulfoaluminate cement clinker, 12 parts of steel slag powder, 15 parts of blast furnace slag powder, 15 parts of natural gypsum, 4 parts of limestone powder, 2.2 parts of calcium nitrate, and 0.22 parts of citric acid. However, during the preparation process, calcium nitrate (2.2 parts) is added during the steel slag grinding stage, and citric acid is added in step 2) to be dry-mixed with other raw materials. Other preparation and curing methods are the same as in Example 1.

[0065] Comparative Example 6 A low-carbon sulfoaluminate cement is prepared in a manner similar to that of Example 1, except that the grinding process in step 1) includes: placing steel slag powder and composite activator together in a ball mill at a speed of 400 r / min for 50 min.

[0066] Comparative Example 7 A low-carbon sulfoaluminate cement is prepared in a manner largely the same as in Example 1, except that the amounts of calcium nitrate and citric acid in the composite activator (2.42 parts) are as follows: (a) 1 part calcium nitrate, 1.42 parts citric acid; (b) 2.3 parts calcium nitrate, 0.12 parts citric acid.

[0067] Comparative Example 8 A low-carbon sulfoaluminate cement is prepared in a manner similar to that of Example 1, except that the amounts of steel slag powder and composite activator in the raw material system weighed in step 1) are: (a) 24 parts of steel slag powder and 1.2 parts of composite activator; (b) 5 parts of steel slag powder and 3 parts of composite activator.

[0068] The low-carbon sulfoaluminate cements obtained in Examples 1-5 and the cements obtained in Comparative Examples 1-8 were subjected to tests for compressive strength, setting time, and chloride ion diffusion coefficient of cement mortar. The specific testing methods are as follows: When making test blocks using the above-mentioned low-carbon sulfoaluminate cement paste, standard sand was added at a cement-sand ratio of 1:3 to make cement mortar test blocks with dimensions of 40 mm × 40 mm × 160 mm. The blocks were then placed in a standard curing chamber. After 6 hours, they were demolded and transferred to a constant temperature water bath for curing. When the test blocks reached the corresponding curing age, the compressive strength test was conducted according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in the table below.

[0069] Table 1. Performance test results of cement specimens obtained in Examples 1-5 and Comparative Examples 1-8

[0070] As can be seen from Example 1 and Comparative Examples 1 and 2, the samples using the stepwise grinding pre-modification process of this invention and with raw material activity meeting the standards exhibit significantly better strength and chloride ion penetration resistance at all ages. Comparative Example 1, by adding the activator only at the dry mixing stage, lacked the synergistic activation effect of the grinding process, resulting in insufficient removal of the inert layer of the steel slag and inadequate dissolution of active components, leading to a decrease in strength. This verifies that introducing the activator during the grinding stage is more beneficial for the deep activation of the steel slag. Comparative Example 2, using solid waste raw materials with lower activity, showed slow strength development and deteriorated durability, indicating that the solid waste activity index is also a necessary prerequisite for stable performance meeting the standards.

[0071] As can be seen from Examples 1 and Comparative Examples 3 and 4, when only calcium nitrate or citric acid is used as an activator, the overall performance of the cement is significantly worse than that of the composite activating scheme, and it is impossible to simultaneously ensure early strength performance and stable development of later strength. Comparative Example 3, using only calcium nitrate, although accelerating early hydration through ionic interactions, lacks complexation regulation, resulting in uneven crystallization and coarse morphology of the hydration products, leading to limited strength improvement. Comparative Example 4, using only citric acid, exhibits an excessively strong retarding effect, severely inhibiting the early hydration process, significantly prolonging the setting time, and failing to effectively break down the inert layer of steel slag, resulting in insufficient activation of solid waste activity. This indicates that the combination of calcium nitrate and citric acid can form a good synergistic effect, verifying the necessity and technical advantages of the composite activator component design of this invention.

[0072] As can be seen from Examples 1 and Comparative Examples 5 and 6, the timing of the addition of the activator components and the grinding process significantly affect the activation effect of steel slag. Comparative Example 5 only included calcium nitrate in the steel slag grinding stage, while citric acid was added later, in the dry-mixing stage. Citric acid could not complete the pre-modification and regulation of the fresh surface of the steel slag during grinding, significantly weakening the synergistic effect and resulting in insufficient activation of the steel slag and a significant decrease in strength at all ages. Comparative Example 6 used a one-step co-grinding process, resulting in insufficient effective contact depth between the activator and the steel slag, and the overall cement performance was significantly lower than that of Example 1.

[0073] As can be seen from Example 1 and Comparative Examples 7 and 8, when the composition ratio of the composite activator and the ratio of steel slag to activator deviate from the limits of this invention, the overall performance of cement decreases significantly, and it is impossible to balance activation efficiency and performance stability.

[0074] The results above demonstrate that this invention, by introducing a specific steel slag cementitious activator during the grinding stage, can effectively promote and improve the early hydration reaction of the cement-solid waste composite system, thus meeting the engineering requirements for rapid hardening and early strength. The raw material and activation systems employed not only activate the later-stage activity of steel slag and blast furnace slag, promoting secondary hydration reactions, but also optimize the stability and microstructure of hydration products, forming a denser microstructure. This alleviates the common problems of weak later-stage strength growth in traditional sulfoaluminate cement and high-solid-waste-content systems, while significantly improving the erosion resistance and long-term durability of cement materials.

[0075] In summary, this invention, through an optimized solid waste system and composite activator technology, effectively coordinates the early strength characteristics and long-term performance stability of sulfoaluminate cement while achieving high-value-added resource utilization of industrial solid wastes such as steel slag and ore slag. It provides an effective technical approach to address the durability shortcomings of traditional sulfoaluminate cement and the performance degradation issues arising from solid waste utilization.

[0076] The above embodiments are merely illustrative and do not constitute a limitation on the scope of protection of this invention. Guided by the technical concept of this invention, those skilled in the art can make reasonable adjustments and improvements to the process parameters, reagent types, or operating procedures without departing from the spirit and scope defined by the claims. Such modifications all fall within the protection scope of this invention.

[0077] The embodiments of the present invention have been described above. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims. All of these forms are within the protection scope of the present invention.

Claims

1. A method for preparing low-carbon sulfoaluminate cement, characterized in that, Includes the following steps: 1) Weigh out all raw materials, and the weight percentages of each raw material include: 30-98 parts of sulfoaluminate cement clinker, 1-42 parts of steel slag powder, 1-42 parts of blast furnace slag powder, 12-21 parts of gypsum, 1-8 parts of limestone powder, and 1.8-4.6 parts of composite activator; the composite activator contains calcium nitrate and citric acid. The steel slag powder has a 7-day activity index of not less than 50% and a 28-day activity index of not less than 60%; the blast furnace slag powder has a 7-day activity index of not less than 70% and a 28-day activity index of not less than 95%. 2) The composite activator and steel slag powder are ground to obtain modified steel slag powder; the grinding process adopts a step-by-step grinding process, the specific steps of which include: first grinding the steel slag powder at a speed of 350~400 r / min; then adding the composite activator and grinding together at a speed of 400~450 r / min; 3) Dry mix the weighed sulfoaluminate cement clinker, gypsum, limestone powder, modified steel slag powder and blast furnace slag powder evenly to obtain the low-carbon sulfoaluminate cement; In the composite activator, the mass ratio of calcium nitrate to citric acid is (5~15):

1.

2. The preparation method according to claim 1, characterized in that, The composite activator also contains triisopropanolamine, which has a mass ratio of 0.05 to 0.12:1 with calcium nitrate.

3. The preparation method according to claim 1 or 2, characterized in that, When the steel slag powder content is 12-42 parts, the mass ratio of steel slag powder to composite activator is 1:0.1-0.

5.

4. The preparation method according to claim 1 or 2, characterized in that, In step 2), the grinding time of steel slag powder is 5~15min, and the combined grinding time after adding the composite activator is 30~60min.

5. The preparation method according to claim 1 or 2, characterized in that, The CaO content in sulfoaluminate cement clinker is 36–64 wt.%, and the Al₂O₃ content is 20–36 wt.%; the specific surface area is 400–450 m². 2 / kg, density is 3~3.8 g / cm³ 3 .

6. The preparation method according to claim 1 or 2, characterized in that, The steel slag powder contains 23-41 wt.% CaO and 28-49 wt.% Fe2O3; its specific surface area is 320-400 m². 2 / kg, density is 3.2~4.0 g / cm³ 3 The gypsum is natural gypsum, with a CaO content of 35~63 wt.% and an SO3 content of 41~73 wt.%; the limestone powder has a CaO content of 32~56 wt.% and an SiO2 content of 14~25 wt.%; and the blast furnace slag powder has a CaO content of 35~62 wt.% and an SiO2 content of 23~41 wt.%.

7. The preparation method according to claim 1 or 2, characterized in that, The specific surface area of ​​the gypsum is 350~400 m². 2 / kg; the density of limestone powder is 2.5~3.2 g / cm³. 3 The density of blast furnace slag powder is 2.5~3.0 g / cm³. 3 Specific surface area is 380~440m² 2 / kg.

8. The preparation method according to claim 1 or 2, characterized in that, The obtained low-carbon sulfoaluminate cement is mechanically stirred with water, wherein the mass ratio of water to dry material is 0.4~0.5, to obtain a uniform low-carbon sulfoaluminate cement paste.

9. The green low-carbon sulfoaluminate cement prepared by the preparation method according to any one of claims 1 to 8, characterized in that, Its initial setting time is 25-30 min, final setting time is 35-40 min, 1-day compressive strength is 25-35 MPa, 3-day compressive strength is 35-45 MPa, 28-day compressive strength is 43-50 MPa, 90-day compressive strength is 45-55 MPa, and 28-day chloride ion diffusion coefficient is ≤1.0×10⁻⁶. -12 m 2 / s.

Citation Information

Patent Citations

  • Low-carbon and low-clinker cement based on double-excitation system and preparation method of low-carbon and low-clinker cement

    CN122562364A

  • Method and system for producing low-alkalinity new-mineral-system sulphoaluminate cement with steel slags

    WO2020211546A1